Oposición libre vs libre designación al Cuerpo de Inspectores de Educación. De la Transición a la democracia. - Tébar Cuesta, Fernando (Avances en Supervisión Educativa, 2024)
We present the modalities of access to the Educational Inspectorate in the period considered with the objective of contributing to an Education Inspectorate that is more aware of its past and therefore more efficient, summarizing the current empirical basis and discussing questions of validity and reliability of the access processes in relation to the effectiveness of the research. Although, once again, yesterday's solutions are today's problems, the situations of patrimonialization of the public administration, and especially the use of public jobs for the benefit of the different political groups, were the general trend in the period before the Spanish Constitution of 1978. There have been two different periods, one in which the Inspectorate was abolished and yet numerous access processes to the Educational Inspectorate were carried out, and the current period, which is the logical consequence of social progress and the democratic concept, and which is characterized by access through competitive examination.